A systematic review to determine the optimal type and dosage of land-based exercises for treating knee osteoarthritis. (April 2014) - Smith, Toby; Kirby, Edward; Davies, Leigh
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Exercise has been acknowledged as an effective non-pharmacological intervention for osteoarthritis. Consensus regarding the type of exercise i.e., aerobic or resistance, weight bearing or non-weight bearing, and dosage i.e., frequency, loading, duration, or intensity, is yet to be reached. Objective: The purpose of this review was to address two questions: (1) is there a difference in clinical outcomes between different exercise programmes; and (2) what is the optimal dosage of exercises for people with knee osteoarthritis. Methods: A systematic review was conducted. A study of published (AMED, CINAHL, MEDLINE, EMBASE, PubMed, and the Cochrane Library) and unpublished literature (WHO International Clinical Trials Registry Platform, current controlled trials and the United States National Institute of Health Trials Registry, and Open Grey) was undertaken in January 2013. Studies assessing the clinical outcomes of different types and dosages of exercise for people with osteoarthritis of the knee were included. Methodological quality was assessed using the critical appraisal skills programme (CASP) randomized controlled trial (RCT) appraisal tool. Results: Ten studies assessing 958 knees from 916 participants were included. Exercise significantly improved pain and function for people with knee osteoarthritis. There was no significant difference in outcomes for different types of exercise i.e., aerobic versus resistance, weight bearing versus non-weight bearing. There was no significant difference in respect to the intensity of exercise i.e., high- versus lower-intensity resistance or aerobic exercises. The quality of the literature was moderate to high. Conclusions: While exercise appears to improve symptoms and optimize function for people with knee osteoarthritis, the optimal form and dosage of exercise remains unknown. Funding: None. PROSPERO Registration Number: CRD42012002811.